Chemogenomic approaches to drug design : docking-based virtual screening of nematode GPCRs for potential anthelmintic agents - Masuka, Raban Wilfred (Department of Chemistry, 2016)
Among common problems affecting human health and veterinary medicines, helmintic infections are major. The pathogens affect 550-750 Million people worldwide, and affect childhood growth, pregnancies, and development of the intellect. Helminths affects the well-being of animals as well including livestock and reduce the animal populations. However, the current anthelmintics are no longer as effective and some strains have developed resistance thus increasing the need for new anthelmintics. Unfortunately, not too much information is available detailing the physiology of helminths. The published genomic sequence of nematode Caenorrhabdtis elegans as well the primary sequence of the FLP18R1 G-Protein Coupled Receptor are available. GPCRs play a significant role as targets for therapeutics and are responsible for signal transduction in cells. Thus, nematode GPCRs offer an alternative target to design new anthelmintics. Unfortunately, very little information exists about these targets and there are no known x-ray or NMR structures. In this work, the 3D structure of nematode GPCR receptor (FLP18R1) was determined using homology modeling using the beta-2-adrenergic receptor as a template. The homology model developed had 24.87 % sequence identity with the template. Explicit membrane molecular dynamic simulations were used to optimize and refine the helices of the model over 100 ns. The homology model was of acceptable quality.